Education Cash Transfer and High School Enrollment in Indonesia - Pasman Caniago; Elfindri Elfindri; Delfia Tanjung Sari (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2021)
Smart Indonesia Program (Program Indonesia Pintar/PIP) is a policy made by the Indonesian government that aims to guarantee and ensure every child has access to a decent education and has the same learning opportunities at all levels of education. However, the enrollment rate at the secondary level, especially in senior high school, is still far from the government target, as stated on the National Medium-Term Development Plan of 2015-2019. This study aims to understand the PIP’s impact on the probability of getting an education in Indonesia's Senior High School (Sekolah Menengah Atas/SMA). This study applied logistic regression analysis to determine PIP's effect regarding children's opportunities at the age of 16-18 years old to attend school. This study uses data from 16-18 years old children who belong to the households categorized as the 40% lowest expenditure group in Susenas 2017, to align with the PIP’s target based on Integrated Database (Basis Data Terpadu /BDT). The result reveals that 16-18 years old children in households included in the lowest 40% of expenditure who receive PIP have higher and significant probabilities of attending high school level in Indonesia. Administration of PIP to 16-18 years old children from the 40% lowest expenditure group will increase their chance to participate in senior high school/equivalent by 15-25 percent. The characteristics of the beneficiaries such as gender, education level of the head of the household, and residence area can affect PIP's performance in escalating the probability of 16-18 years old children attending senior high school/equivalent.